Mitral valve replacement for Libman–Sacks endocarditis in a patient with antiphospholipid syndrome secondary to systemic lupus erythematosus. Issue 4 (3rd April 2018) - Nakasu, Akio; Ishimine, Tohru; Yasumoto, Hiroshi; Tengan, Toshiho; Mototake, Hidemitsu
Abstract: Libman–Sacks endocarditis is a relatively rare sterile verrucous vegetative lesion observed in systemic lupus erythematosus (SLE)/antiphospholipid syndrome (APLS) patients. Most patients with this condition are asymptomatic. Here we report a case of a 46-year-old woman with APLS secondary to SLE complicated with frequent thromboembolic events due to a mitral valve mass. We performed minimally invasive mitral valve replacement with a mechanical prosthetic valve, and she was successfully discharged 14 days after surgery. Thus, Libman–Sacks endocarditis may be an indication for mitral valve replacement.